Análise do parque urbano do Ingá e suas funcionalidades em Maringá - PR/Brasil - Lisboa, Jonatas Diniz [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
In Brazil, mostly, cities that are not contaminated with efficient bodies that manage and maintain systems of public spaces or green areas for leisure and recreation. The creation of urban parks contributes to urban sustainability, with places for sport and leisure, and offers benefits of quality of life in the urban space, also contributing to alleviate possible social tensions, as they provide a space for the approximation of human beings with nature. Keeping ideas in mind, this monograph seeks to understand the role of the Ingá urban park for the city of Maringá-PR, and for its population. For this, an analysis was made of the public equipment that is used on the site, the role of the park in the aesthetic composition of the landscape, as well as its local importance for leisure and sport, and preservation of the environment.

No Brasil, majoritariamente, as cidades não contam com órgãos eficientes que gerenciem e mantenham sistemas de espaços públicos ou de áreas verdes voltadas para lazer e recreação. A criação de parques urbanos contribui para a sustentabilidade urbana, com locais para esporte e lazer, e oferecendo benefícios a qualidade de vida no espaço urbano, contribuindo também para amenização de possíveis tensões sociais, pois proporcionam um espaço de aproximação do ser humano com a natureza. Tendo estas ideias em mente, a presente monografia busca compreender o papel do parque urbano do Ingá para cidade Maringá-PR, e para a sua população. Para isto, foi feita uma análise dos equipamentos públicos que são utilizados no local, o papel do parque na composição estética da paisagem, assim como sua importância local de lazer e esporte, e preservação do meio ambiente.
Analysis of the Ingá urban park and its features in Maringá - PR/Brazil
Keywords: Ingá park; Urban park; Environment; Geography; Parque do Ingá; Parque urbano; Maringá-PR; Meio ambiente; Geografia